Enhanced Reliability Assessment in Distribution Network Planning via Optimal Double Q Strategy with Explicit Topology-Variable Consideration - Jiang, J.; Luo, Q.; Xu, Z.; Li, H.; Gao, C. (Radioengineering Society, 2025)
In the planning of distribution networks, assessing reliability is essential for enhancing network design and selection. This research introduces a new distribution network planning model that aims to balance economic performance and system reliability through a double Q strategy. The model integrates important reliability assessment metrics with the optimized design of the distribution network's topology. To address the computational difficulties associated with traditional power flow calculations in complex network configurations, this study employs a linearized power flow method, which enhances the model's practicality and adaptability. Additionally, recognizing the discrete decision-making aspects of the planning issue, a mixed-integer linear programming model is developed. By utilizing the adaptive ε-constraint method, the study investigates the global Pareto frontier between reliability and cost, offering valuable decision-making support for planners. Results from case studies demonstrate that the proposed method effectively lowers the overall construction and operational costs of the distribution network, albeit with a minor reduction in system reliability.
Keywords: Reliability assessment; distribution network planning; double Q strategy; linearized power flow method; adaptive ε-constraint